Using Emergy to Assess the Business Plan of a Small Auto-parts Manufacturer in Brazil - Almeida, C.M.V.B.; Carvalho, N.; Giannetti, F. Agostinho, B. F. (Journal of Environmental Accounting and Management, 2026)
The initiative of evaluating products using the supply chain standpoint to help reducing the environmental and socioeconomic impact connected with manufacturing has been recently acknowledged. Yet, there are no studies making an allowance for the various types of small businesses that operate in the sphere of influence of large supply chains to fill gaps or serve consumers with particular needs. These little companies that, in general, have no control over the decisions made along the supply chain have to reconcile their production processes with the decisions taken by the leading companies. This work evaluates a case of induced product change, and its cost regarding the use of environmental resources and energy of a small company working in the Brazilian automotive aftermarket. This approach also looks into an underexplored aspect in the use of emergy accounting in which the studied system is at the end of the production chain, and confirms the thought that actions in the central supply chain may have advantageous effects that can go beyond what was expected by the decision maker. The simulation performed for the period 2014-2025, according to the company’s commerce plan, shows that the earlier the products change is completed, the greater would be the profit, the greater the resources and energy savings, and, consequently, the greater ecoefficiency of the business.